Charge-transfer crystal with segregated packing structure constructed with hexaarylbenzene and tetracyanoquinodimethane. Issue 33 (9th August 2021) - Ando, Rempei; Jin, Mingoo; Ito, Hajime
Abstract : Charge-transfer (CT) crystals bearing segregated domains between the hexaarylbenzene and TCNQ are a promising platform for developing new organic functional solid-state materials. Abstract : Charge-transfer (CT) crystals bearing segregated domains between the electron donor and acceptor molecules are a promising platform for developing new organic functional solid-state materials. However, there is limited diversity in the segregated structures of CT crystals. Herein, we report a novel structure of a CT crystal using hexaarylbenzene (HAB) and tetracyanoquinodimethane (TCNQ) as the electron donors and acceptors, respectively. Single-crystal X-ray diffraction (XRD) studies revealed that hexapyridylbenzene and TCNQ form a segregated layer in crystalline media, and the CT feature of TCNQ was observed in terms of the observed chemical bond lengths in the crystal.